PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2010-2013) (Students' Journal of Accounting and Banking, 2015)
The company's main goal according to the theory of the firm is to maximize wealth or firm value (value of the firm). Maximize the value of the company is very important for a company, because by maximizing the value of the company means also maximizing share holder wealth is the main goal of the company. This study aimed to determine the effect of profitability, dividend policy, foreign investment, enterprise scale and firm age on firm value in the companies listed in Indonesia Stock Exchange. The company's main goal is to maximize the wealth or the value of the company. Maximizing the value of the company is very important for a company, because by maximizing the value of the company also means maximizing shareholder wealth is the main aim of the company. This study aims to determine the effect of firm size, leverage, profitability, and dividend policy on firm value in companies listed in Indonesia Stock Exchange 2011-2013 period. The population in this study is the manufacturing companies listed on the Stock Exchange during 2011-2013. This study uses secondary data obtained from the annual report www.idx.co.id. Samples were selected using purposive sampling technique. Data were analyzed using multiple linear regression analysis. Results of hypothesis testing showed that the positive effect of firm size is not significant to the value of the company. Leverage positive and significant effect on firm value. Profitability positive and significant effect on firm value. Dividend policy significant positive effect on firm value. Keywords: Firm Size, Leverage, Profitability, Dividend Policy and The Value of The Company